Artificial language, natural history: Speech, sign, and sound in the emergence of Damin. (September 2017) - Fleming, Luke
Abstract: The Lardil male initiate language, Damin, is a unique linguistic system. Traditionally employed by second-order male initiates, or warama, Damin has a lexicon of no more than 150 distinct morphemes and a phonology employing ejectives and clicks—sound types unattested in other Australian languages. These esoteric features have led scholars to see Damin as an artificial or invented language. I argue that the label of linguistic artificiality forestalls explanation as much as it aids it. In this paper I show that the eccentric features of Damin developed in an emergent and unplanned manner in which conventionalized paralinguistic phonations became semanticized as they were linked up with a signed language, Marlda Kangka, employed by first-order male initiates, or luruku . Highlights: Critique of natural, as opposed to artificial, language as proper object of study. Damin male initiate speech register frequently labeled an 'invented language.' Initiate signed language (Marlda Kangka) served as a substrate for Damin. Phonetically marked forms initially used as paralinguistic accompaniments to sign. Damin is socially emergent rather than the singular invention of an individual.